Current phase 1/2 research for neovascular age-related macular degeneration. Issue 3 (May 2015) - Pecen, Paula E.; Kaiser, Peter K.
Abstract : Purpose of review: The purpose of this review is to provide an update of phase 1 and 2 clinical trials in neovascular age-related macular degeneration that are either currently underway or recently completed by the end of 2014. Recent findings: Three gene therapy options are currently in early clinical trials, administered via intravitreal (AAV2-sFLT01) or subretinal (AVA-101 and RetinoStat) injection to express angiogenesis inhibitors. Several eye drops are being developed for topical administration for various angiogenic inhibitors, including regorafenib, squalamine lactate, and PAN-90806. Early development of systemic administration options may be intravenous (iSONEP) or oral (X-82). Initial study of local radiation therapy may be via proton beam irradiation or stereotactic radiotherapy. Several intravitreal injections are being studied including human immuno-conjugate molecule (hl-con1), abicipar pegol, PF582, DE-120, ESBA 1008, and REGN2176-3. Summary: Numerous treatment options of neovascular age-related macular degeneration are in phase 1/2 clinical trials including gene therapy, eye drops, systemic dosing, localized irradiation, and various intravitreal injections. Future phase 3 trial results will be observed closely to determine which of these therapies will be the next novel treatment of neovascular age-related macular degeneration.